2003
DOI: 10.3748/wjg.v9.i10.2240
|View full text |Cite
|
Sign up to set email alerts
|

Construction of expression systems forflaAandflaBgenes ofHelicobacter pyloriand determination of immunoreactivity and antigenicity of recombinant proteins

Abstract: AIM:To clone flagellin genes A (flaA) and B (flaB) from a clinical strain of Helicobacter pylori (H pylori) and to construct prokaryotic expression systems of the genes and identify immunity of the fusion proteins. METHODS:The flaA and flaB genes from a clinical H pylori isolate Y06 were amplified by high fidelity PCR. The nucleotide sequences of target DNA amplification fragments from the two genes were sequenced after T-A cloning. The recombinant expression vector pET32a inserted with flaA and flaB genes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…It was reported that there are many protective antigens against H pylori, such as UreB, HpaA, VacA, CagA, NapA, FlaA, FlaB and heat shock protein (HSP) [8][9][10][11][12][13]23] . Due to cross-antigens against HSP in different sibling bacteria [23] , 7 kinds of protective antigens of H pylori except for HSP were selected in our research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that there are many protective antigens against H pylori, such as UreB, HpaA, VacA, CagA, NapA, FlaA, FlaB and heat shock protein (HSP) [8][9][10][11][12][13]23] . Due to cross-antigens against HSP in different sibling bacteria [23] , 7 kinds of protective antigens of H pylori except for HSP were selected in our research.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the gene orders of ureB, hpaA, napA, flaA and flaB have been confirmed as highly conservative, while the gene order of vacA can mutate moderately between signal peptide zone (S) and intermedial zone (M), and the mutations of CagA gene order are mainly located at the 3' terminal repeat [8,9,12,13,15] . Our research focused on the carrying rates and expression level of the 7 kinds of genes of H pylori from the clinical H pylori in China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations